Internationalizing the Curriculum and all Students’ Learning - Leask, Betty (International Higher Education, 2014)
Internationalization of the curriculum has the potential to connect broader institutional agendas focused on internationalization with student learning. However, the focus of internationalization of the curriculum in policy and practice is more on what some students will experience than on what all students will learn. An internationalized curriculum focused on student learning is defined by two main characteristics. First, it will be connected to the different cultures and practices of knowing, doing and being in the disciplines through the active engagement of faculty in the process of internationalizing the curriculum. Second, faculty who do not have the experience, skills or knowledge required to internationalize the curriculum will be supported by expert facilitators in the process of defining intended internationalized learning outcomes and assisting all students to achieve them.